(In reply to
re: incomplete solu - thinking better by pcbouhid)
Induction doesn't always have to proceed by showing that if a proposition is true for n then it is true for n + 1. In this case, given that we know the divisibility is different for even and odd n, we note that:
f(0) = 12 is divisible by 3,
f(1) = 155 is divisible by 5.
Then f(n+2) - f(n) = 11 × 14n(142 - 1) = 11 × 3 × 5 × 13 × 14n is divisible by both 3 and 5, and the result follows by induction.
(f(n) divisible by 3 implies f(n+2) divisible by 3; f(n) divisible by 5 implies f(n+2) divisible by 5.)